Graphitic carbon nitride nanosheets for solution processed non-volatile memory devices. Issue 33 (1st August 2019) - Wang, Ruopeng; Li, Huilin; Zhang, Luhong; Zeng, Yu-Jia; Lv, Ziyu; Yang, Jia-Qin; Mao, Jing-Yu; Wang, Zhanpeng; Zhou, Ye; Han, Su-Ting
Abstract : A memory device is demonstrated based on g-C3 N4 nanosheets with a non-volatile behavior and a bipolar switching characteristic. Abstract : Resistive random-access memory (RRAM) is the most promising research direction of the next generation non-volatile memory (NVM) devices, and seeking novel materials as the active layer can facilitate RRAM device development. Two-dimensional graphitic carbon nitride (g-C3 N4 ) nanosheets with a mass of carrier trapping sites are employed as the active layer of RRAM devices. Solution processed memory devices show good stability and reliability, and the fabricated g-C3 N4 -based RRAM devices show a non-volatile behavior and a bipolar switching characteristic with an ON/OFF ratio of 10 3, a low operation voltage and good retention capability. In addition, by means of controlling the compliance current precisely, multi-level data storage can be realized. The mechanism of the RRAM devices is thought to be carrier trapping assisted hopping, which is verified by atomic force microscopy in the electrical mode. This work demonstrates that g-C3 N4 nanosheet based RRAM devices provide a novel direction for low energy and high density data storage devices.